PENGUNAAN MICROSOFT EXCEL DALAM PERHITUNGAN INDEKS KEPUASAN MASYARAKAT (Study Kasus Pada Unit Pelayanan Sim Satlantas Kota Bekasi) - Feri Prasetyo H (Jurnal Khatulistiwa Informatika, 2014)
Microsoft Excel is a spreadsheet application that can be used in business applications Community satisfaction index, is a data and information about the level of community satisfaction with the results obtained from the public opinion in obtaining the services of officials of public service providers by comparing the expectations and needs. 14 elements of the "relevant", "valid" and "reliable", as the minimal element that must exist for the basic measurement of community satisfaction index is the following service procedures, service requirements, Clarity care workers, service personnel discipline, responsibility care workers, ability officer service, speed of service, a ministry of Justice, Courtesy and friendliness of staff, fairness of service charges, cost of service assurance, service assurance schedules, Leisure environment, the Security service. The purpose of this study was to Knowing how much the level of community satisfaction in the service, to determine the performance of service personnel, in this study using quantitative methods of data processing is to be anggka the provision of respondents based on factors which are then processed to determine the calculation of HPI to get the results .Keyword: Community Satisfaction Index, Public Service Management.